PENGARUH KARAKTERISTIK SOSIAL EKONOMI TERHADAP PRODUKSI JAMBU METE DI DESA BANTEA KECAMATAN GU KABUPATEN BUTON TENGAH - Mustari, La Ode Muhammad (Media Agribisnis, 2019)
The study discusses economic social characteristic influence on the production of Jambu mete in Bantea Village, Subdistrict of Gu Central Buton Regency. This study discusses the influence of socio-economic characteristics of the production of cashew in Bantea Village, Subdistrict of Gu Central Buton Regency. This study was conducted over three months starting in June until August 2015. The population of this research is that there are cashew farmers, sample taking by the number 28 cashew farmers. Data were collected through interviews using a questionnaire and analyzed using descriptive analysis. The results of the study concluded that the cashew nut farmers in Bantea Village, Subdistrict of Gu Central Buton Regency show that socioeconomic factors (education, farming experience, number of dependents and land) significantly affected the production of cashew nut farmers. By him it was suggested to farmers, is expected to further enrich the knowledge and insights of the farming handled, especially in terms of the handling of pests and plant diseases, and the government is expected to give more attention to farmers, whether it be the handling of low production due to high rainfall and plant pests and diseases. Keywords: production, socio-economic, cashew.